Bimbingan Teknis Pengembangan Materi Muatan Lokal Budaya Mentawai SDN 02 Matotonan Kabupaten Kepulauan Mentawai - Zulfa Zulfa; Juliandry K. Junaidi; Liza Husnita; Ranti Nazmi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2022)
This service activity is basically based on the problem that the strengthening and development of local cultural materials that are integrated into the 2013 curriculum has not been maximized since the implementation of the 2013 Curriculum and strengthened by the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 79 of 2014 concerning Local Content of the 2013 Curriculum provides opportunities for teachers to develop local cultural content material, even though Mentawai has a culture that is quite interesting and widely known by the public and even the international community and it is almost as if Mentawai culture is taught in schools. The purpose of this service is to strengthen the local Mentawai culture which is integrated into teaching materials. The method used to achieve the target of this service is by providing assistance, training, and mentoring to teachers in the development of local content material for Mentawai culture. The results achieved in the service that has been carried out are that teachers have creativity in developing local content material for Mentawai culture which is contained in learning devices such as in the Learning Implementation Plan. From the whole series of service activities that have been carried out, it can be concluded that the development of teaching materials based on local content of Mentawai culture is very necessary, for that it needs to be poured into learning tools to be implemented in actual learning activities.